2016
DOI: 10.1016/j.cmi.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the safety and immunogenicity of live attenuated and inactivated hepatitis A vaccine in healthy Chinese children aged 18 months to 16 years: results from a randomized, parallel controlled, phase IV study

Abstract: For large-scale immunization of children with hepatitis A (HA) vaccines in China, accurately designed studies comparing the safety and immunogenicity of the live attenuated HA vaccine (HA-L) and inactivated HA vaccine (HA-I) are necessary. A randomized, parallel controlled, phase IV clinical trial was conducted with 6000 healthy children aged 18 months to 16 years. HA-L or HA-I was administered at a ratio of 1: 1 to randomized selected participants. The safety and immunogenicity were evaluated. Both HA-L and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Inactivated and live attenuated HA vaccines account for half of the market share of the Chinese national immunization programme. HA-L involves only a single dose; therefore, it is less expensive and easier to implement than the classical two-dose HA-I vaccine, but the disadvantage is that the virus in the live attenuated vaccine can possibly replicate and be actively excreted [15]. Both HA vaccines used in this trial included freeze-dried HA-L and HA-I preparations that had shown good safety and immunogenicity profiles during phase I, II and III clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inactivated and live attenuated HA vaccines account for half of the market share of the Chinese national immunization programme. HA-L involves only a single dose; therefore, it is less expensive and easier to implement than the classical two-dose HA-I vaccine, but the disadvantage is that the virus in the live attenuated vaccine can possibly replicate and be actively excreted [15]. Both HA vaccines used in this trial included freeze-dried HA-L and HA-I preparations that had shown good safety and immunogenicity profiles during phase I, II and III clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This was a randomized, double-blind, parallel controlled phase IV clinical trial conducted in counties in Jiangsu Province, China, where an HA epidemic had not occurred for nearly 3 years. The trial methods and sample size calculation have been previously reported [15]. This trial recruited three groups of participants: 18e36 months of age (infant group), 3e16 years old (children group) and 16 years old or more (adult group).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…81 In a randomized, parallel controlled, phase IV study in China, 12 (25%) of the 48 randomized selected participants who received HepA-L tested positive for HA antigen in stool samples within 28 d after vaccination, and the detection rates of vaccine HAAg in stool samples on d 1, 7, 14, 21 and 28 postvaccination were not significantly different. 43 In another Chinese study, HAV was isolated from 70% (53/75) of tool samples from children whose roommates received HepA-L, but elevated ALT was not detected among these children, suggesting that HepA-L could cause horizon transmission of HAV, but could not induce hepatitis A clinical disease. 82 Further surveillance should be implemented on the possibility of horizon transmission of HepA-L and its implication in hepatitis A elimination in countries using HepA-L.…”
Section: Factors Associated With Immunogenicity Of Hepamentioning
confidence: 97%
“…[33][34][35][36][37] Seroconversion of anti-HAV could be achieved after two doses of HepA-I among almost all children regardless of the manufacture of the vaccine. 5,22,28,29,[37][38][39][40][41][42][43] The anti-HAV seroconversion rate could reach approximately 95% at 14-30 d after the first dose of HepA-I, 22,29,41,44,45 and the second-dose could greatly elevate the anti-HAV level postvaccination. 22,37,43 A similar seroconversion rate after one-dose vaccination was reported between HepA-I and HepA-L among children and adults, 39,42,43 and GMC was much higher after two doses of HepA-I compared with onedose of HepA-I or HepA-L. 42 The nature of the prompt immune response after HepA vaccination is important for its use for PEP.…”
Section: Antibody Response Following Hepa Vaccinationmentioning
confidence: 99%